Spatial profiling of the placental chorioamniotic membranes reveals upregulation of immune checkpoint proteins during Group B Streptococcus infection in a nonhuman primate model - Manuel, Gygeria; Coleman, Michelle; Orvis, Austyn S.; Munson, Jeff; Li, Amanda; Kapur, Raj P.; Li, Miranda; Li, Edmunda; Armistead, Blair; Rajagopal, Lakshmi; Adams Waldorf, Kristina M. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Preterm birth is a leading cause of neonatal mortality, which is often complicated by intrauterine infection and inflammation. We have established a nonhuman primate model of Group B Streptococcus (GBS, Streptococcus agalactiae) infection-associated preterm birth. Immune checkpoints are modulators of the immune response by activating or suppressing leukocyte function and are understudied in preterm birth. The objective of this study was to spatially profile changes in immune protein expression at the maternal-fetal interface during a GBS infection with a focus on immune checkpoints. Methods Twelve nonhuman primates (pigtail macaques, Macaca nemestrina) received a choriodecidual inoculation of either: 1) 1-5 X 108 colony forming units (CFU) of hyperhemolytic/hypervirulent GBS (GBSΔcovR, N=4); 2) an isogenic/nonpigmented strain (GBS ΔcovRΔcylE, N=4); or, 3) saline (N=4). A Cesarean section was performed at preterm labor or 3 days after GBS infection or 7 days after saline inoculation. Nanostring GeoMx® Digital Spatial Profiling technology was used to segment protein expression within the amnion, chorion, and maternal decidua at the inoculation site using an immuno-oncology panel targeting 56 immunoproteins enriched in stimulatory and inhibitory immune checkpoint proteins or their protein ligands. Statistical analysis included R studio, Kruskal-Wallis, Pearson and Spearman tests. Results Both inhibitory and stimulatory immune checkpoint proteins were significantly upregulated within the chorioamniotic membranes and decidua (VISTA, LAG3, PD-1, CD40, GITR), as well as their ligands (PD-L1, PD-L2, CD40L; all p<0.05). Immunostaining for VISTA revealed positive (VISTA+) cells, predominantly in the chorion and decidua. There were strong correlations between VISTA and amniotic fluid concentrations of IL-1β, IL-6, IL-8, and TNF-α (all p<0.05), as well as maternal placental histopathology scores (p<0.05). Conclusion Differential regulation of multiple immune checkpoint proteins in the decidua at the site of a GBS infection indicates a major perturbation in immunologic homeostasis that could benefit the host by restricting immune-driven pathologies or the pathogen by limiting immune surveillance. Protein expression of VISTA, an inhibitory immune checkpoint, was upregulated in the chorion and decidua after GBS infection. Investigating the impact of innate immune cell expression of inhibitory immune checkpoints may reveal new insights into placental host-pathogen interactions at the maternal-fetal interface.